PENGARUH PLYOMETRIC TRAINING TERHADAP PERUBAHAN KEKUATAN DAN KECEPATAN PADA TIM BOLA VOLI SMA NEGERI KEBERBAKATAN OLAHRAGA - Nurul Hikmah; Yunita Angraeni Arana (LPPM Universitas Abdurrab, 2024)
Background: In volleyball, passing, jumping, smash and block movements are very much needed strength and very high speed. To increase strength and speed is to practice plyometric training, namely countermovement jumps and lateral cone hops with sprints. It aims to be able to perform techniques with high jumps, and speed when taking the ball. Method: This type of research is a pre-experimental research. This research is a research method used to describe changes in the strength and speed of volleyball players after providing plyometric training. The design used in this study is one group pretest-posttest design. The sample in this study was taken with a purposive sampling technique and then a total sample of 20 people was obtained and each treatment was given plyometric training. Results: The results showed that the provision of plyometric training could result in an increase in volleyball player strength with an average statistical result of pre test 231.00 to 300.00 in the post test and an increase in speed with an average pre-test statistic 4.6730 to 3, 9340 in the post test. T Test results show that giving plyometric training can result in increased strength and speed. Conclucion: So the conclusion is that plyometric training has a significant influence on the level of strength and speed of volleyball players in senior high school of sport Makassar. Based on the results of significant calculations P = 0,000 or <0.05. Suggestions for athletes and trainers is to use plyometric training that has been programmed to increase strength and speed, in order to improve athlete performance and support game success. Keywords: Plyometric Training, strength, speed, Countermovement Jump, Lateral Cone Hops with Sprint.